2007
DOI: 10.1080/15402000701557383
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Psychosocial Stress on Sleep: A Review of Polysomnographic Evidence

Abstract: This systematic review examines the effect of diverse psychosocial stressors on polysomnographic measures of sleep. Sixty-three articles were located and categorized in terms of the types of stressors imposed. Experimental stress resulted in fairly consistent changes: decreases in slow wave sleep, REM sleep, and sleep efficiency (SE), as well as increases in awakenings. Data were limited in terms of response to non-experimental stressors, except for the case of post-traumatic stress disorder (PTSD) on sleep, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
273
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(297 citation statements)
references
References 68 publications
17
273
3
4
Order By: Relevance
“…Furthermore, the concurrent validity between MaSQuDI-17 and the two questions about the "perceived restfulness at wake up" and "sleep duration" confirms previous findings that demonstrated the bidirectional relationship between distress and unhealthy sleep [7,9,13,15]. Indeed, our study subjects suffering from a sleep disorder reported a worse restfulness on waking as well as a shorter sleep duration and scored higher on the MaSQuDI-17 than the "normal" sample of subjects.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, the concurrent validity between MaSQuDI-17 and the two questions about the "perceived restfulness at wake up" and "sleep duration" confirms previous findings that demonstrated the bidirectional relationship between distress and unhealthy sleep [7,9,13,15]. Indeed, our study subjects suffering from a sleep disorder reported a worse restfulness on waking as well as a shorter sleep duration and scored higher on the MaSQuDI-17 than the "normal" sample of subjects.…”
Section: Discussionsupporting
confidence: 77%
“…Many studies have demonstrated the bidirectional relationship between distress and unhealthy sleep defined as sleep with a duration less than 7 hours or longer than 8 hours [7,9,13,14]. Evidence indicates that emotional distress is associated with changes in sleep architecture, total sleep time, sleep quality, sleep efficiency, rapid eye movement sleep, sleep onset latency, and slow wave sleep [9,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos hallazgos coinciden con otros estudios que señalan estos síntomas como problemas de alta prevalencia en estudiantes de medicina y los relacionan con el estrés y la carga académica 21,22,23 . Un estudio que comparó los problemas de sueño en estudiantes de medicina, derecho y economía, concluyó que los estudiantes de medicina tenían la peor calidad de sueño 22 y esto se ha vinculado con la salud mental y el nivel de estrés 23,24 .…”
Section: -24unclassified
“…Insomnia has become more and more common, and the effects are extremely negative to a student's education. Research on sleep disturbances in undergraduate medical students is of particular interest because of the known relationship between sleep and mental health [1] and the ic demands of medical training can Insomnia is nowadays being recognised as a public health concern which affects the of life of millions of people around term physical and mental th altered mood, concentration, and memory.Inadequate sleep quantity and quality have been associated with poor school performance, mental health problems, poor sociability, behavioural problems, the development of obesity and its accompanying comborbidities Sleep disorders such as Obstructive sleep apnea (OSA) syndrome is characterized by repetitive episodes of upper airway obstruction that occur during sleep, usually associated with a reduction in blood oxygen saturation [4] is a n complication which affects the population worldwide. [5]Subsequently, the social and professional aspects of life are also being affected because of a deterioration of general condition with a decrease in intellectual abilities and cognitive behaviour.…”
Section: Introductionmentioning
confidence: 99%